GERAK TARI JAUK MANIS DALAM FOTOGRAFI EKSPRESI DENGAN TEKNIK STROBO LIGHT - Balayasa, I Wayan Open Yusa; Nindhia, Cokorda Istri Puspawati; Candrayana, Ida Bagus (Retina Jurnal Fotografi, 2021)
Tari Jauk Manis is a dance that symbolizes the figure of a king who was wandering and have unique movement, authoritative and meek. Beginning to pull the creators took the theme of the dance Jauk Manis this because the movement is a unique and interesting to be recorded through the medium of photography, the Purpose of this creation is to visualize the movement Tari Jauk Manis to in photographic expression with the technique of Strobe Light into a work that is unique and interesting as well as to know the different kinds of movement in dance Jauk Manis.Tari Jauk Manis have a costume like a Line dance, just dance Jauk Manis use the mask which are white, topknot (king's crown), and gloves with long nails. Complete clothing used in the staging tari Jauk Manis namely trousers white, stewel, kamben white, clothes, srimping, kris, awiran, lamak, badong, topknot, and the mask is colored white. Creator through the method of observation as well as conducting interviews of motion Dance Jauk Manis, then continued the process of shooting to the location. With the Technique of Strobe Light used in the photo shoot Tari Jauk Manis, From the results of the photoshoot done the photo selection and proceed to the next stage until the end to the process of creation of an exhibition and a presentation. To visualize the Motion Tari Jauk Manis in photographic expression with the technique of Strobe Light is a very unique and interesting creators have to do observation direct observation to determine the movement of what is commonly used in the use of the Technique Strobe Light. The movement on the dance Jauk Manis this is 22 the movement of the selected creator of the 15 parts of the movement that made the photo with the Technique of Strobe Light. Keywords : Jauk Manis Dance Movement, Expression Photography, Strobe Light